Effects of agricultural-grade magnesium chloride as an anesthetic agent and a gonad sampling technique on white scar oysters (Crassostrea belcheri) - PARICHART NINWICHIAN; THIDARAT KHUMRAK; PHEERAPON CHAIKEEREE; NIRANDON PHUWAN (Anais da Academia Brasileira de Ciências)
Abstract The effects of agricultural-grade magnesium chloride (MgCl2) and gonad sampling on white scar oysters (Crassostrea belcheri) were evaluated. Oysters were anesthetized with 4 MgCl2 solutions at 4 concentrations (0, 30, 50, or 70 g L-1) for 24 h. The most effective solution was subsequently used to study the effects of gonad sampling using needles of different sizes (20G, 22G, or 24G) on C. belcheri. The results revealed no significant differences in the percentage of anesthetized oysters after exposure to 30, 50, or 70 g L-1 MgCl2 for 24 h. However, the 50 g L-1 MgCl2 solution was most effective at inducing anesthesia in C. belcheri, with 86.67±6.67% after 15 h. No significant differences in mortality rates were observed 7 days after anesthesia among the oysters immersed in 30, 50, or 70 g L-1 MgCl2. The 20G, 22G, and 24G needles enabled gonad sampling for sex determination, with no mortality in any treatment group after 15 days. Therefore, a cost-effective anesthesia protocol and gonad sampling method was established for C. belcheri. These protocols are valuable for C. belcheri broodstock management, facilitating effective breeding and other research studies requiring C. belcheri survival after tissue sampling.